Uji Efektivitas Antimikroba Dettol, Betadine, dan Harpic terhadap Staphylococcus Aureus dengan Metode Difusi Cakram - Citra Bunga Lestari; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This research was conducted to assess the antimicrobial activity of Dettol, Betadine, and Harpic against the bacterial growth of Staphylococcus aureus using the disk diffusion technique. The method involved placing sterile paper disks soaked with each test agent onto agar media previously inoculated with S. aureus. Observations revealed that Harpic formed the widest inhibition zone, measuring 15 mm, followed by Dettol with a 12 mm zone, and Betadine with the smallest at 8 mm. Meanwhile, the control disk exhibited no inhibitory effect (0 mm). These results suggest that Harpic has the highest antimicrobial potential among the three products tested in suppressing Staphylococcus aureus growth.